The Plio-Pleistocene sequence of Oued Boucherit (Algeria): A unique chronologically-constrained archaeological and palaeontological record in North Africa. (1st November 2021) - Duval, Mathieu; Sahnouni, Mohamed; Parés, Josep M.; van der Made, Jan; Abdessadok, Salah; Harichane, Zoheir; Cheheb, Razika Chelli; Boulaghraif, Kamel; Pérez-González, Alfredo
Abstract: Located within the Beni Fouda intramontane basin, the Oued Boucherit area (Guelta Zerga, North East Algeria) hosts a unique succession of archaeological and palaeontological deposits spanning from the late Pliocene to the Early Pleistocene. While the recent work by Sahnouni et al., (2018) mostly focused on the two Oldowan archaeological levels AB-Lw and AB-Up, we present here an updated overview of the entire Oued Boucherit sequence, resulting from a long-term multidisciplinary investigation that started in 1992. In particular, we report for the first time a description of the oldest palaeontological levels dated to >3 Ma, and of the uppermost archaeological level hosting Acheulean artefacts. The age-depth model initially proposed by Sahnouni et al. (2018) was further extended to chronologically constrain the whole sequence, which spans from ∼3.93 Ma at the bottom to ∼1.65 Ma at the top. The Oued Boucherit sedimentary sequence records the earliest evolutionary steps of lithic technology, with early Oldowan assemblages at Ain Boucherit dated to about 2.44 Ma (AB-Lw) and 1.92 Ma (AB-Up) Ma, followed by the ∼1.77-1.72 Ma assemblages of Ain Hanech and El Kherba showing more derived features, and the appearance of the Acheulean technology, dated to ∼1.67 Ma. This chonostratigraphic framework indicates that the Oued Boucherit area (<1 km 2 ) hosts the oldest Oldowan and Acheulean assemblages identified so far in North Africa. It is also especially striking that their chronology is somewhat close to the earliest Oldowan and Acheulean evidence found in East Africa and South Africa. Moreover, at least six fossiliferous levels ranging from ∼3.78 to 1.77-1.72 Ma have been identified and stratigraphically positioned within the sequence. They represent a unique opportunity to study not only the evolution of large mammal faunal assemblages in North Africa, but may also give some key insights about the evolution of palaeoecological and palaeoenvironmental conditions in the region throughout the Late Pliocene to the Early Pleistocene. While the number of well-dated Plio-Quaternary faunal assemblages in North Africa remains somewhat limited, the Oued Boucherit sequence may be used as a reference for regional biochronological inferences. Highlights: Oued Boucherit (OB) records a succession of six palaeontological and four archaeological levels. Their estimated ages range from ∼3.78 Ma to ∼1.67 Ma. Three Oldowan levels dated to ∼2.44 Ma, ∼1.92 Ma and ∼1.77 Ma have been identified. OB documents the oldest Acheulean evidence found in North Africa, dated to ∼1.67 Ma. A multiple African origin scenario for stone tool manufacture and use is plausible.